The relationship between stock and real estate prices in Turkey: Evidence around the global financial crisis - Asli Yuksel (Central Bank Review (CBR), 2016)
Research on the relationship between stock and real estate prices focuses on two transmission mechanisms, namely the wealth and credit-price effects. This paper uses the 2007 global financial crisis as a natural experiment and examines whether the relationship between real estate prices and stock prices has changed after the outbreak of the crisis by using data from the Turkish market. The results based on a threshold cointegration framework indicate that while both effects exist during the pre-crisis period, only a credit-price effect is observed during the crisis period. Moreover, the findings are sensitive to whether or not one allows for asymmetric error correction.
Keywords: C22; E44; G11; 330; Credit-price effect; Wealth effect; Threshold error-correction model; Causality